IN VITRO ANTIDIABETIC AND IN VIVO ANTIDIARRHEAL ACTIVITY OF Oncoba Spinosa ROOTS - M, Prasanth Kumar; V, Suba; B, Ramireddy; P, Srinivas Babu (INDONESIAN JOURNAL OF PHARMACY, 2015)
The different extracts of O.spinosa (Flacourtiaceae) were screened for in-vitro antidiabetic activity. Of all the extracts tested, ethanolic extract showed highest alpha amylase inhibition ranging from 8.64+0.66% to 79.94+0.65% and alpha glucosidase inhibition ranging from 14.12+0.51% to 78.68+0.36% when studied at concentrations 62.5-1000Î¼g/mL. The ethanolic extract was subjected to antidiarrheal activity and diarrheal severity was reduced significantly by 15.81% in 100mg/kg group, 30.45% in 200mg/kg group and 74.37% in 400mg/kg group in castor oil induced diarrhea model. In castor oil induced enteropooling, the extract at doses 200mg/kg and 400mg/kg showed 33.46% and 42.44% inhibition of intestinal accumulation. In the charcoal meal test, the distance travelled by charcoal meal was significantly reduced by the extract at doses 200mg/kg and 400mg/kg (P<0.01). The overall results tend to suggest the antidiabetic and antidiarrheal activities of O. spinosa.Key word : in vivo, in vitro, antidiabetic, antidiarrheal, O.spinosa, roots